2015
DOI: 10.1111/cod.12367
|View full text |Cite
|
Sign up to set email alerts
|

Individual prevention courses for occupational skin diseases: changes in and relationships between proximal and distal outcomes

Abstract: The results are consistent with the assumption that IP courses provide a range of benefits for people with occupational contact dermatitis. Changes in distal outcomes may be influenced by changes in proximal outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(21 citation statements)
references
References 37 publications
0
20
1
Order By: Relevance
“…In general, telephone interviews results in more complete data, compared to mailed questionnaires [ 37 ], which was confirmed in our study, which had very few missing data. However, extreme responses in self-assessment questions are generally more frequent in telephone interviews than in mailed questionnaires [ 37 ], which may explain the higher baseline mean values for the constructs in our study, compared with other studies using mailed HeiQ questionnaires [ 18 , 33 , 38 , 39 ]. This may indicate that our results reflect a slight overestimate.…”
Section: Discussioncontrasting
confidence: 56%
See 2 more Smart Citations
“…In general, telephone interviews results in more complete data, compared to mailed questionnaires [ 37 ], which was confirmed in our study, which had very few missing data. However, extreme responses in self-assessment questions are generally more frequent in telephone interviews than in mailed questionnaires [ 37 ], which may explain the higher baseline mean values for the constructs in our study, compared with other studies using mailed HeiQ questionnaires [ 18 , 33 , 38 , 39 ]. This may indicate that our results reflect a slight overestimate.…”
Section: Discussioncontrasting
confidence: 56%
“…Previous findings have shown that patients experience a great deal of anger and anxiety shortly after diagnosis [ 32 ]. Most participants in the study reported here had had diabetes for a number of years, so it is very likely that they developed over time good self-management skills through trial and error, life experience and interaction with health-care providers [ 33 ]. Mastering their diabetes could be reflected in emotional improved wellbeing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First of all, controls could not be taken for ethical and legal reasons as the prevention program forms part of the regular structures of patient care since 2007. Thus, the uncontrolled, longitudinal pre/post-test design as applied in comparable studies in Germany in the last 15–20 years, remains a feasible study design for this type of health services research [1517, 23, 25, 50, 51]. However, an uncontrolled study cannot sufficiently prove the effectiveness of an intervention and the obvious methodological limitations regarding internal validity have to be considered for the interpretation of the results.…”
Section: Discussionmentioning
confidence: 99%
“…In this follow-up, we have focused on distal primary outcomes that change and can only be measured a comparatively long time after the intervention. In contrast, more proximal outcomes (e.g., socio-cognitive variables and attitudes which might serve as determinants and prerequisites of skin protection behavior) are more directly affected by an intervention [51, 54], and changes can be observed immediately or shortly after an intervention. Analyzing these proximal outcomes allows more in-depth insights into effects of the prevention program and into behavior change processes of the patients.…”
Section: Discussionmentioning
confidence: 99%